The Effect of the Inquiry-Based Learning Model on Students’ Learning Outcomes in Science with the Aid of Video Media in the Fourth Grade at SDN Petapa - Miftahul Janna; Nuraini Nuraini; Putriwanti Putriwanti; Sinta Satria Dewi Pendit (FKIP - Universitas Riau, 2026)
This study aims to determine the effect of the guided inquiry learning model assisted by video media on students’ learning motivation and learning outcomes in Science subjects in Grade IV of SDN Petapa. The background of this research is the low learning motivation of students and the suboptimal use of instructional media in Science learning. The research employed a quasi-experimental method with a Control Group Design, involving two classes: an experimental class that received the guided inquiry model assisted by video media, and a control class that received conventional instruction. Data were collected using a learning motivation questionnaire that had passed validity and reliability testing. The results showed a significant increase in the posttest scores of the experimental class compared to the control class. The paired sample t-test obtained a significance value of 0.000 < 0.05, indicating that the guided inquiry learning model assisted by video media has a significant effect on improving students’ learning motivation. The use of video media helps students understand Science concepts more concretely, attractively, and easily, while the inquiry approach encourages students to actively engage in investigative and discovery-based learning processes.